Thaba ea Tlholo designing a high performance cycling facility in the mountains of Lesotho - Van Rensburg, Kathleen (My University, 2019)
Cycling is arguably the fastest growing sport in South Africa, from grass roots programs empowering communities through bicycling, to the large organised cycling events that attract thousands of participants. From cycle sports tourism generating millions of Rands in revenue, to Dimension Data sponsoring Africa’s first Tour de France team. Cycling is on the rise. But despite all of this, South Africa, and by extension Africa, barely features on the international stage of professional cycling. Even Team Dimension Data, whilst being Africa’s first cycling team to compete in major tours, consists of 78% non-African riders. Aside from cycling being an expensive sport, we don’t have sufficient terrain or facilities in place to adequately produce world class riders. Aspiring individuals are forced to seek training at international facilities in the hopes of being selected for a foreign team. A localised facility coupled with a cycle sports youth development program would make South African/ African professional cycling more attainable, more affordable and produce better cyclists. ABSTRACT I’m proposing a high performance cycling facility based in Lesotho. Lesotho is an emerging sports tourism location with many avid mountain bikers making the journey to tackle the terrain. The facility as well as a proposed World Tour stage could significantly boost the local economy and secure Lesotho as a sporting destination. The facility itself would be located at the top of the Mahlasela pass in the Maluti mountains. This placement takes advantage of the twisting mountain roads and high altitude as an ideal training ground to boost performance. The facilities’ program is to centre around the cyclist’s training and personal needs as well as house laboratory facilities to analyse and assess performance. The architecture is to be inspired by local Lesotho dwellings with a focus on environmental sustainability
This document is submitted in partial fulfillment for the degree: master of Architecture (Professional) at the University of the Witwatersrand, Johannesburg, South Africa, February 2019